The street-jihadi spectrum: Marginality, radicalization, and resistance to extremism - Sandberg, Sveinung (European journal of criminology, 2024)
For over a decade, jihadi terrorism in Europe, and the recruitment of Europeans to fight for ISIS in Syria, have increasingly involved marginalized youths from a social context of street culture, illegal drug use and crime. Existing theoretical models of the crime-terrorism nexus and radicalization arguably do not sufficiently explain the fluid and dynamic ways by which the street cultural come to be politico-religiously violent. This paper provides a novel retheorization, the street-jihadi spectrum, which is better placed to explain a wide range of behaviours, from the merely stylistic to the spectacularly violent. On the street culture end it includes subcultural play with provocative jihadi symbols and on the jihadi end the terrorism of ?gangster-jihadists?. We emphasize that the spectrum, consisting of a multitude of confluences of street and jihadi cultures, also includes resistance to jihadism.